The ICC Preventive Function with Respect to the Crime of Aggression and International Politics (2017)
In most national systems, criminal liability arises when a person agrees to commit an ordinary crime, participates in the design of a criminal plan, or contributes to establishing the conditions necessary for its execution. The extension of the scope of criminal law at the national level to criminalize preparatory acts for ordinary crimes, regardless of whether the crime is subsequently completed or even initiated, has been used, to an important extent, to confront situations in which a group of persons engages in criminal conduct to achieve economic (e.g., trafficking of human beings, drugs, and weapons, or money laundering) or political (e.g., terrorism) goals.